Trabeculectomy in young Nigerian patients (2002)
The results of 89 trabeculectomies performed on 56 patients under the age of 30 years were reviewed. Data collected included age, sex, type or glaucoma, number of years of glaucoma before surgery, visual acuity, intraocular pressure, complications of surgery, presence of a filtering bleb and follow-up period. Complete success, denoted by a postoperative lOP of 21mmHg or less without medical therapy, occurred in 50 eyes (56.2%). Qualified success, in which lOP was 21mmHg or less with additional medical therapy occurred in 31 eyes (34.9%) and failure, in which lOP was greater than 21mmHg in spite of medical treatment occurred in 8 eyes (8.9%). Success was therefore achieved in 91.1 % attaining an lOP of 21mmHg or less, with or without additional medical therapy. The most statistically significant factor was age groups in which the highest success rate of I00% was achieved in the age group 20-29 years. The difference in the success rate across the age groups was statistically significant (x2 = 8.04, p = 0.0 I). Fornix based conjunctival flaps were also found to be associated with a statistically significant higher success rate (97.9%) as opposed to limbal based flaps (85.4%), X2= 4.81, p = 0.03. Males in the study group had a significantly higher success rate (97%) than females (78.3%), X2= 5.86, P = 0.011. A success rate of 100% was recorded in patients with developmental glaucoma, 86.1% in congenital glaucoma and 33.3% in secondary glaucoma. All the repeat trabeculectomies had congenital glaucoma. The presence of a bleb, although it had a higher success rate (93.4%) compared with the absence of a bleb (84.6%), was not statistically significant (x2 = 1.19, P = 0.27). Complications of surgery were mostly transient.